The EuroPrevall outpatient clinic study on food allergy: background and methodology. Issue 5 (23rd February 2015) - Fernández‐Rivas, M.; Barreales, L.; Mackie, A. R.; Fritsche, P.; Vázquez‐Cortés, S.; Jedrzejczak‐Czechowicz, M.; Kowalski, M. L.; Clausen, M.; Gislason, D.; Sinaniotis, A.; Kompoti, E.; Le, T.‐M.; et al.
Abstract Background The EuroPrevall project aimed to develop effective management strategies in food allergy through a suite of interconnected studies and a multidisciplinary integrated approach. To address some of the gaps in food allergy diagnosis, allergen risk management and socio‐economic impact and to complement the EuroPrevall population‐based surveys, a cross‐sectional study in 12 outpatient clinics across Europe was conducted. We describe the study protocol. Methods Patients referred for immediate food adverse reactions underwent a consistent and standardized allergy work‐up that comprised collection of medical history; assessment of sensitization to 24 foods, 14 inhalant allergens and 55 allergenic molecules; and confirmation of clinical reactivity and food thresholds by standardized double‐blind placebo‐controlled food challenges (DBPCFCs) to milk, egg, fish, shrimp, peanut, hazelnut, celeriac, apple and peach. Results A standardized methodology for a comprehensive evaluation of food allergy was developed and implemented in 12 outpatient clinics across Europe. A total of 2121 patients (22.6% <14 years) reporting 8257 reactions to foods were studied, and 516 DBPCFCs were performed. Conclusions This is the largest multicentre European case series in food allergy, in which subjects underwent a comprehensive, uniform and standardized evaluation including DBPCFC, by a methodology which is made available for further studies in food allergy. The analysis of this population will provide information on the different phenotypes of food allergy across Europe, will allow to validate novel in vitro diagnostic tests, to establish threshold values for major allergenic foods and to analyse the socio‐economic impact of food allergy.